A Descriptive study of selected prostituted women survivors in Davao City - Edillon, Riza Mae P.
This is a descriptive study of the lives of prostituted women survivors before, within, and after prostitution. It presents the various stages in the life of a survivor of prostitution. This is a case study method using primary data gathered through in-depth interviews. It was conducted in Davao City at the Drop-in Center and Main Office of Talikala Incorporated, a non-government organization providing assistance and education to prostituted women. Participants of the study were five(5) prostituted women survivors, all of whom are members of Lawig Bubai, an organization of prostituted women organized with the help of Talikala Incorporated. I used the support system theories of Caplan, Germain, and Silverman to explain how prostituted women survivors cope with their difficulties while they were in prostitution and when they left prostitution. Social support system provide people opportunities for feedback about themselves, and it aids people to cope with their struggle when they are undergoing a change in roles. I also used the extrinsic motivation theory of Twain in explaining that these women's motivation to get out of prostitution. Motivation is an important mechanism that drives th people to do all means to achieve a goal. And in the case of these prostituted women, their goal was to become a survivor of prostitution. Results of the study reveal that all five(5) prostituted women survivors came from poor families, were not able to finish school, and started working at an early age. Reasons for entering prostitution are deception (sex trafficking), unexpected family problems (like a child getting sick, stepfather needing to be operated) being left behind by irresponsible partners, no other choice to earn a big amount of money except through prostitution since unable to finish school, and poverty. Within prostitution, these women have experienced various forms of abuse coming from their family, customers, pimps, floor managers, and from people in the community. These women have employed coping mechanisms such as resorting to drugs and alcohol, and to pouring out their emotions in order to survive these struggles while they were still in prostitution. The presence of a support system such as Talikala and lawig Buabai were essentially helpful in the coping and surviving of these women. Reasons for living involved being educated by Talikala, concern for their children, being asked and offered to leave by a live-in partner or a customer, realization that prostitution is not there for them to be in it already. After prostitution these women were able to find new jobs and started a new phase in their life. These women are looking forward to a future wherein they would have stable jobs, and they will be able top see their children finish school. Starting a new face in their life, these women are driven to achieve and realize their plans. In conclusion, the study was able to found out that there are factors the pushed these women to enter prostitution; that they have experienced and endured struggles within prostitution by employing coping mechanisms and with the help of support systems; that there are factors that made them decide to leave prostitution; that they were able to survive their detachment from prostitution because of coping mechanisms and institutional support; and finally that these women have plans waiting to be realized now that they are out of prostitution.